Testes de desempenho funcional em mulheres com dor femoropatelar - Araujo, Samara Guimarães (2022)
Introduction: Patellofemoral pain (PFD) is characterized by anterior knee and/or peripatellar pain, which intensifies during activities that require the eccentric action of the quadriceps muscle, especially during functional activities such as descending stairs, ramps and squatting. Therefore, it is important to include these activities in the evaluation. Objective: The present study aimed to evaluate women with PFD taking into consideration their performance in functional performance tests and lower limb isometric strength. Methodology: This study evaluated 100 women (50 with PFD and 50 controls), during the execution of the following functional performance tests: Triple hop, Vertical Jump, Single leg squat, Step Down, Y balance test, Lunge test and running. Dynamic valgus was also assessed in the tests. The isometric muscle strength of the following muscle groups: hip abductors, hip extensors, lateral rotators, knee extensors, eversions, and plantar flexors were evaluated. In order to understand the perception of function regarding PFD, the following scales were applied: Activity of Daily Living Scale (ADLS), Anterior Knee Pain Scale (AKPS). Results: The Y balance test, Triple hop test, Vertical Jump test, and running showed lower performance in the DFP group. An increase in dynamic valgus during Triple Hop Test, Vertical Jump test and running was observed in the PFD group, and a poorer perception of function was observed in the control group. For all lower limb muscle groups, the PFD group showed a reduction in peak strength, and this reduction was clinically relevant. Conclusion: The Y balance test, triple hop test, vertical jump test, and running should be included in the physical therapy evaluation, in addition to aspects of lower limb muscle strength